(untitled) (Caring: Indonesian Journal of Nursing Science, 2023)
"Oplosan Liquor" is an Indonesian term that refers to illegally made alcoholic beverages created by mixing ethanol or alcohol with other ingredients. The ethanol content in these beverages is uncontrolled and can pose a significant threat to human health. Consuming oplosan liquor with high levels of ethanol can cause alcohol poisoning and, in extreme cases, death. Methanol intoxication can impact patient outcomes, influencing factors such as appropriate treatment, adequate medical and psychological support, and the patientâ€™s ability to avoid future methanol exposure. Differences in outcomes exist between patientsÂ mitted for the first time and those experiencing readmission. This case report aims to elucidate the unique distinctions in patient outcomes between those admitted for the first time and those readmitted after methanol intoxication. Materials and Methods: This case report describes an instance that occurred in the same patient, detailing their medical history, clinical symptoms, diagnostic tests, and treatment provided during their stay in the emergency department. Variances in outcomes were observed between two patients, with one succumbing to the effects and the other managing to survive. We share our experience in treating a patient with methanol intoxication during their initial admission and subsequent readmission to a hospital in Indonesia. Indonesian people are acquainted with a drink called "Oplosan Liquor," which is fermented to achieve an alcohol content of up to 90%. This beverage is consumed by many young people who lack knowledge about the use of alcoholic beverages.